Superalloys 718, 625, 706 and Various Derivatives (1994) 1994
DOI: 10.7449/1994/superalloys_1994_683_694
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Laves Phase in Nb-Hardened Superalloys

Abstract: The possibility of forming the topologically close-packed Laves phase has been investigated in various Ni-base superalloy systems that contain a significant amount of Nb. Simplified alloy compositions consisting of various combinations of major alloying elements, including Cr, Fe, and Co, were prepared; a high level of Nb was added in each alloys to simulate the dendritic segregation in the real casting process. In addition to the fee dendrites, the as-cast microstructure through a slow solidification rate dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The formation of Laves phase is a result of Nb, Si and Mo segregation during solidification, where these alloying elements are rejected from the dendrites into the interdendrites [29,30]. Chang et al [31] suggested that the relatively high contents of Cr and Fe in IN718 are the necessary condition for Laves phase, aside from the segregation of Nb. The chemical composition of Laves might differ with solidification condition, but is generally referred as (Ni,Fe,Cr) 2 (Nb,Mo,Ti).…”
Section: Lavesmentioning
confidence: 99%
“…The formation of Laves phase is a result of Nb, Si and Mo segregation during solidification, where these alloying elements are rejected from the dendrites into the interdendrites [29,30]. Chang et al [31] suggested that the relatively high contents of Cr and Fe in IN718 are the necessary condition for Laves phase, aside from the segregation of Nb. The chemical composition of Laves might differ with solidification condition, but is generally referred as (Ni,Fe,Cr) 2 (Nb,Mo,Ti).…”
Section: Lavesmentioning
confidence: 99%
“…This constitutes a fact evidencing the difference in the relative intensity of different crystalline peaks for the same phase (e.g., 2θ = 75 • in BM and 2θ = 91 • in WM for austenite phase). The texture observed in the WM region is due to the columnar grains and the orientation of the intermetallic particles that change the reflection angle of the XRD pattern for each phase [21,[31][32][33]. distribution in the BM are different when compared to the WM.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…Additionally, X-ray diffraction (XRD) analyses using a Bruker diffractometer model D8 Advance ECO operated with Cu Kα at 40 kV and 25 mA and the sweep angle range (2θ) from 30 • to 120 • with a scanning speed of 2 • /min were used to analyze the phases and intermetallics present in the material. The crystalline peaks of the XRD spectra were identified based on powder diffraction files (PDF) 330945, 893890 and 653574, and a literature survey [31][32][33][34]. The percentages of intermetallics in each one of the welding regions were quantified based on the ASTM E1245.…”
Section: Microstructure Characterizationmentioning
confidence: 99%
“…The formation of Laves phase is a result of Nb, Si and Mo segregation during solidification, where these alloying elements are rejected from the dendrites into the interdendrites [22,27]. Chang et al [28] suggested that the relatively high contents of Cr and Fe in IN718 are necessary for forming Laves phase, aside from the segregation of Nb. The chemical composition of Laves might differ with solidification condition, but is generally referred as (Ni,Fe,Cr) 2 (Nb,Mo,Ti).…”
Section: Lavesmentioning
confidence: 99%